2019
DOI: 10.1080/15548627.2019.1569925
|View full text |Cite
|
Sign up to set email alerts
|

Redundancy of human ATG4 protease isoforms in autophagy and LC3/GABARAP processing revealed in cells

Abstract: Macroautophagy/autophagy is a cellular degradation pathway that delivers cytoplasmic material to lysosomes via double-membrane organelles called autophagosomes. Lipidation of ubiquitin-like LC3/ GABARAP proteins on the autophagosome membrane is important for autophagy. The cysteine protease ATG4 executes 2 LC3/GABARAP processing events: priming of newly synthesized pro-LC3/ GABARAP to enable subsequent lipidation, and delipidation/deconjugation of lipidated LC3/ GABARAP (the exact purpose of which is unclear i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
153
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(158 citation statements)
references
References 47 publications
5
153
0
Order By: Relevance
“…Previous researches suggested that the miR-376 mediated ATG4C silencing could suppress autophagy in breast cancer cells and hepatocarcinoma cells [31,32]. Recently, there was data implied that ATG4C had a limited role in autophagy [50]. In the current work, we observed that LC3-II expression was significantly reduced in the presence of BafA1 in sh-ATG4C cells, indicating impaired autophagic flux.…”
Section: Discussionsupporting
confidence: 44%
“…Previous researches suggested that the miR-376 mediated ATG4C silencing could suppress autophagy in breast cancer cells and hepatocarcinoma cells [31,32]. Recently, there was data implied that ATG4C had a limited role in autophagy [50]. In the current work, we observed that LC3-II expression was significantly reduced in the presence of BafA1 in sh-ATG4C cells, indicating impaired autophagic flux.…”
Section: Discussionsupporting
confidence: 44%
“…Beclin-1, a crucial regulator of autophagy, forms a complex with other autophagy proteins in order to mediate autophagosome assembly and to increase intracellular autophagic flux [ 33 , 34 ]. During autophagy, cytosolic microtubule-associated protein 1 light chain 3-I (LC3-I) is converted into microtubule-associated protein 1 light chain 3-II (LC3-II) and recruited to the autophagosomal membrane, with such conversion being an indicator of autophagosome formation [ 35 , 36 ]. In our study, the overexpression of MKP-5 rescued the PA-induced reduction in Beclin-1 observed at both 9 and 12 h post-treatment in Rin-m5f cells, whereas LC3-II levels were augmented only at 12 h post-PA treatment in Rin-MKP-5 relative to Rin-PC cells ( Figure 4 D).…”
Section: Resultsmentioning
confidence: 99%
“…However, this model is complicated by the fact that ATG4B C74A very strongly binds to its substrates, acting as a sink that depletes LC3/GABARAPs from the cytoplasm. More recently, cell lines edited by clustered regularly interspaced palindromic repeats (CRISPR) technology, where one or a combination of all four mammalian ATG4 family members have been deleted, were reported [37,38]. In addition, a cell line with deletion of all major LC3/GABARAP proteins has been produced and studied with regards to their resistance to external stresses [44,45].…”
Section: Atg4b As Drug Targetmentioning
confidence: 99%
“…Here, we propose the autophagy-specific ATG4 proteases as a druggable class of enzymes that can overcome these limitations. The ATG4 proteases mediate processing of ubiquitin-like Atg8/LC3/GABARAP proteins involved in the formation and maturation of autophagosomes, the functional units of the autophagy pathway [37]. Here, we will perform a critical appraisal of ATG4B as drug target in cancers and discuss tools and reagents available for drug development.…”
Section: Introductionmentioning
confidence: 99%